2015
DOI: 10.1111/jfb.12774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute handling stress on cerebral monoaminergic neurotransmitters in juvenile Senegalese sole Solea senegalensis

Abstract: Juvenile Senegalese sole Solea senegalensis were subjected for short periods to two different types of handling-related stress: air exposure stress and net handling stress. The S. senegalensis were sacrificed 2 and 24 h after the stress events and the levels of serotonin (5-HT), noradrenaline (NA), dopamine (DA) and their respective major metabolites, 5-hydroxyindoleacetic acid (5-HIAA), 3-methoxy-4-hydroxyphenylglycol (MHPG) and 3,4-dihydroxyphenylacetic acid (DOPAC), were measured in three brain regions (tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In fish, Npy has a role in the regulation of feeding (orexigenic) and growth, as well as in the stimulatory control of reproductive processes (Zohar et al ; Shahjahan, Kitahashi, & Parhar, ). Dopamine is an inhibitory system in the control of reproduction in several fish species, including sole (Guzmán et al ) and, in this species, it also appears to participate in responses to challenging stress situations (Costas et al ; Weber et al ). Interestingly, GnIH has a role not only in the control of reproduction, but also in the regulation of food intake and in the mediation of stress responses (Tsutsui, ; Tsutsui & Ubuka, ; Ernst, Lynn, & Bentley, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fish, Npy has a role in the regulation of feeding (orexigenic) and growth, as well as in the stimulatory control of reproductive processes (Zohar et al ; Shahjahan, Kitahashi, & Parhar, ). Dopamine is an inhibitory system in the control of reproduction in several fish species, including sole (Guzmán et al ) and, in this species, it also appears to participate in responses to challenging stress situations (Costas et al ; Weber et al ). Interestingly, GnIH has a role not only in the control of reproduction, but also in the regulation of food intake and in the mediation of stress responses (Tsutsui, ; Tsutsui & Ubuka, ; Ernst, Lynn, & Bentley, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine and norepinephrine are involved in the organization of stress response in vertebrates (Winberg & Nilsson, ). Recent research shows that the brain dopamine level in teleosts increased after being stressed by chasing, handling and air exposure (Gesto et al ., ; Weber et al ., ). Furthermore, Wolkers et al .…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine and norepinephrine are involved in the organization of stress response in vertebrates (Winberg & Nilsson, 1993). Recent research shows that the brain dopamine level in teleosts increased after being stressed by chasing, handling and air exposure (Gesto et al, 2013;Weber et al, 2015). Furthermore, Wolkers et al (2015) demonstrated that territorial resident matrinxã fish (Brycon amazonicus) have a high dopamine level in the hypothalamus of the brain after being subjected to a social challenge stress by introducing an intruder into their territory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fish were suspended in the air for 3 min and were then redistributed in 50 L tanks (two fish/tank). At intervals of 30 min, 2 and 24 h after air exposure, the fish were caught (in pairs, within 15 s) and finally placed in a 10 L tank containing the anaesthetic MET (10 mg/L) before blood sampling [21]. MET was used at this stage for the following reasons: 1) the dose used induces deep anaesthesia within 1.5 min [20], and 2) in S. senegalensis it produces a weaker stress response than other fish anaesthetics and it does not significantly affect cortisol levels 2 and 24 h after exposure [8].…”
Section: Experimental Designmentioning
confidence: 99%